Parent's perceptions of antenatal groups in supporting them through the transition to parenthood - Pilcher, Hilary; Hughes, Anita J. (Midirs, 2014)
Objective: The aim of this study was to explore parents’ experiences and perceptions of their antenatal groups in supporting their needs through the transition to parenthood. Local research ethics approval was obtained before the study commenced. Design: Phenomenology was considered the most appropriate paradigm to interpret participants’ involvement as it considers the essence of individuals’ experiences and fits the holistic model of midwifery. Semi-structured interviews were used to ascertain mothers’ and fathers’ experiences and their perceptions of support needs. Participants: Prospective mothers and fathers were recruited from the community setting by midwives whilst the women were in their last trimester of pregnancy. Interviews were undertaken with both parents together in the early postnatal period, between two and three weeks after the baby’s birth. Findings: Six mothers and five fathers participated in the interviews and several themes emerged from analysis of the transcripts. Parents felt developing a relationship with fewer midwives was important and attending antenatal groups was a way to achieve this. Antenatal groups which were facilitative and flexible seemed to have helped parents prepare and adjust to parenthood. Conclusions and implications for practice: Participants felt antenatal groups have an important role to play in preparation for parenthood and should be universally available. Provision of universal groups may be one way to meet government targets to reduce inequalities, provide choice and improve access for women and families. Although midwives are highly skilled practitioners, additional skills may be required for the role of group facilitator. A focus on these skills within pre- and post-registration education is suggested. A multiagency approach to implement such services, in line with government strategy, may be cost effective and practical as well as promoting ongoing support and interagency collaboration.